The Role of Employee Recovery Performance on Service Recovery Performance and Quality of Service - Tirtana, Diovany; Rahmadhani, Sari (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to evaluate the influence of employee and service recovery performance on service effectiveness in SAMSAT Semarang City. This study explores the empirical model of employee recovery performance, service recovery performance, and quality of service in Public Service Institutions.Methodology/approach: This method uses a quantitative approach, with data collected through surveys of employees directly involved in the service.Results/findings: The results showed that employee recovery performance had a positive effect on service quality, whereas service recovery performance did not impact service quality. The study also found that employee recovery performance serves as a mediator in the relationship between service recovery performance and service quality. Conclusion: This study aimed to explore the role of service recovery performance and employee performance in enhancing service effectiveness at the SAMSAT office in Semarang City. The results indicate that employee recovery performance has a positive effect on service quality, in line with initial expectations. These findings suggest that improving employee recovery performance can strengthen public perceptions of SAMSAT services. Limitations: This study focuses on internal factors, such as employee performance and service recovery, but has not extensively examined external influences on service effectiveness.Contribution: These findings emphasize the importance of training and support for employees in improving customer satisfaction. The results of this study are expected to provide concrete recommendations for service improvement at SAMSAT, as well as open up opportunities for further research on factors that affect the effectiveness of public services.